DMB Machine Reliability Analysis Through Failure Mode Effect Analysis and Reliability Block - Annisa Indah Pratiwi; Boyman Sihombing; Muhamad Sayuti; Nugraha Pradana; Dewih Adetia (OPSI, 2021)
The production process is carried out continuously, it will result in decreased machine capability. When a component on a machine is damaged resulting in the production process being interrupted, the machine's performance depends on the Reliability of the machine or the component. The DMB machine is a sorting machine at PT Etex Building Performance Indonesia, because it is the main machine in the production process and DMB has a high downtime in 2019. Failure Mode effect And Analysis, aims to determine the machine failure factor. Reliability Block Diagram, to determine machine reliability. The results of research with FMEA are Pneumatic with RPN value 60, Decelerator value RPN 64, Accelerator value RPN 56, Hydraulic Table Safety Lock value RPN 48, Roller value RPN 48 Bearing Lifting value RPN 36, Sensor Transfer Dolly value RPN 48, Motor Transfer Template RPN value 36, the Suction Cup is the component that has the lowest RPN value with a value of 30, from the Reliability Block Diagram (RBD) calculation, the DMB machine reliability opportunity value is obtained including 88.42% of the production process for 23 hours, 42.25% of the process for 161 hours of operation. , and decreased by 2.70% when used for 674 hours of operation. Recommended action is to perform maintenance actions with the type of daily care and weekly maintenance.